Active Cycle Breathing Technique Terhadap Fungsional Paru Pasien Post CABG (Laporan Kasus Berbasis Bukti) - Riza Pahlawi; Zahra Sativani (Sarana Ilmu Indonesia (salnesia), 2021)
Coronary Artery Bypass Graft (CABG) is an operative action in cases of coronary heart disease (CHD) by cutting and replacing clogged coronary arteries from healthy vessels taken from the legs, arms, or chest. The main clinical problem that arises in post-CABG patients is decreased lung functional capacity, this is due to shortness of breath, pain, decreased thoracic expansion, sputum retention, and decreased pulmonary ventilation. Active Cycle of Breathing Technique (ACBT) is a physiotherapy modality that can be applied in cardiovascular cases. ACBT is a series of exercises that include breathing exercises, coughing exercises, and exercises to expand the chest. To determine the effectiveness of ACBT in increasing lung functional capacity in Post CABG patients, an electronic database search was performed, namely Pubmed, Cochrane, and Google Schoolar. From the search results, 6 articles were selected that met the criteria, namely 1 article on Pubmed and 5 articles on Google scholar. Based on the results of the research that has been presented, it can be concluded that ACBT can increase the functional capacity of the lungs in post CABG patients as evidenced by the evaluation of the results of the 6 minutes walking test, borg scale, and breath holding time.